European Test Symposium (ETS'05)
DOI: 10.1109/ets.2005.8
|View full text |Cite
|
Sign up to set email alerts
|

Automatic March Tests Generation for Static and Dynamic Faults in SRAMs

Abstract: New memory production modern technologies introduce new classes of faults usually referred to as Dynamic Memory Faults. Although some handmade March Tests to deal with these new faults have been published, the problem of automatically generate March Tests for Dynamic Faults has still to be addressed. In this paper we propose a new approach to automatically generate March Tests with minimal length for both Static and Dynamic Faults. The proposed approach resorts to a formal model to represent faulty behaviors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…In [9], a March test algorithm of length 100N, was proposed for detection of two-cell dynamic faults with two fault-sensitizing operations both applied on the victim or aggressor cells (S aa and S vv ). Note that the proposed test appeared to be redundant, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [9], a March test algorithm of length 100N, was proposed for detection of two-cell dynamic faults with two fault-sensitizing operations both applied on the victim or aggressor cells (S aa and S vv ). Note that the proposed test appeared to be redundant, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, they have proposed minimal March test algorithms for detection of all twooperation single-cell dynamic faults in Random Access Memories, as well as a minimal March test algorithm of length 70N for detection of two-cell dynamic faults with two fault-sensitizing operations both applied on the victim or aggressor cells. The March test algorithm of length 100N, proposed in [9], was reduced by 30N operations. Additionally, it has been shown that the 70N test detects also all realistic unlinked and linked static faults.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], a March test of length 100N was proposed for detection of all two-operation two-cell dynamic faults sensitized by FPs from S aa and S vv . In [10], it was claimed that March 100N is irredundant.…”
Section: Minimal March Test For Two-operation Two-cell Dynamic Faultsmentioning
confidence: 99%
“…In [9] two March test algorithms, March AB1 of length 11N and March AB of length 22N, for classes of single-cell and two-cell dynamic faults, respectively, were proposed improving the length of those proposed in [7]. In [10], a March test algorithm of length 100N was proposed for detection of two-cell dynamic faults with two faultsensitizing operations both applied on the victim or aggressor cells. Note that the proposed test appeared to be redundant, i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation